Return-volatility linkages in the international equity and currency markets - Bill B. Francis; Iftekhar Hasan; Delroy M. Hunter (Bank of Finland, 2002)
This paper, which is motivated by the literature on international asset pricing and recent work on exchange rate determination, investigates dynamic relationships between major currency and equity markets.Using a multivariate GARCH framework, we examine conditional cross-autocorrelations between pairs of national equity markets and related exchange rates.This provides a parsimonious way of testing mean-volatility relationships in currency and equity markets and re-examining the robustness of relationships between equity markets, while controlling for exchange rate effects.We find that the relationship between currency and equity markets is bi-directional, significant, persistent, and independent of the relationship strictly between equity markets, and that it is better captured by the conditional second moments
URN:NBN:fi:bof-20140807567
Keywords: G12; G14; G15; F31; 330; international asset pricing; exchange rate determination; equity markets; relationships between currency and equity markets